2016
DOI: 10.12669/pjms.325.10480
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of first line chemotherapy in patientswith chronic lymphocytic leukemia

Abstract: Objective:Chronic lymphocytic leukemia (CLL) is a heterogeneous disease in terms of survival with and without treatment. Many chemo and immunotherapeutic agents are available to treat this indolent disease. Aim of this study was to determine the outcomes of patients with chronic lymphocytic leukemia treated with different available chemotherapeutic regimens.Methods:All patients with diagnosis of CLL from 2008 to 2013 were included. Data were collected from hospital information system. Objective response rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This age distribution in CLL was consistent with other Pakistani and Indian studies. 17,18 In comparison, median age at diagnosis was slightly higher in Chinese CLL patients (64 years) and Caucasian CLL patients (70-72 years), with <10% patients being diagnosed at age <55 years. [19][20][21] This may reflect referral bias, but may also be suggestive of a genetic predisposition for Indo-Pak CLL patients to present at a younger age, especially considering higher rates of consanguinity in this ethnic group, and can be of significance as this earlier-age CLL may represent a severe disease with worse prognosis and inferior survival outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This age distribution in CLL was consistent with other Pakistani and Indian studies. 17,18 In comparison, median age at diagnosis was slightly higher in Chinese CLL patients (64 years) and Caucasian CLL patients (70-72 years), with <10% patients being diagnosed at age <55 years. [19][20][21] This may reflect referral bias, but may also be suggestive of a genetic predisposition for Indo-Pak CLL patients to present at a younger age, especially considering higher rates of consanguinity in this ethnic group, and can be of significance as this earlier-age CLL may represent a severe disease with worse prognosis and inferior survival outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…22 Regarding gender distribution, male predominance seemed to be a universal characteristic of almost all CLL cohorts. [17][18][19][20][21][22][23][24] CLL has a highly variable natural course with OS ranging from a few years to several decades. The Binet and Rai staging systems still provide a simplified way based on a few simple clinical and laboratory variables, especially in resource-limited healthcare systems, to predict CLL disease progression at diagnosis despite being almost half-a-century old.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 studies met the inclusion criteria (n = 1264 patients) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The summary of the included studies is provided in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The study group had a generally favorable outcome as 22 patients (56%) achieved complete response, 13 (33%) had a partial response, 3 (7.6%) had stable disease, and 1 (2.5%) patient had disease progression. More relapses were seen in the FC group as compared to the FCR group and the authors concluded that the addition of rituximab to the regimen results in improved outcomes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation